WASTEWATER WASHING RICE WITH ONION SKIN ON GROWTH AND PRODUCTION OF CHILLIAN PLANTS: LIMBAH AIR CUCIAN BERAS DENGAN KULIT BAWANG MERAH TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI RAWIT - Siti Mutmainah; Sunarko (Agrifarm : Jurnal Ilmu Pertanian, 2021)
Cayenne pepper (C frutescent L.) is one of the leading horticultural commodities in general. Chili fruit also contains many nutrients that are needed for human health including protein, fat, carbohydrates, calcium (Ca), phosphorus (P), iron (Fe), vitamins and contain alkaloid compounds such as capsicum, flavonoids, and essential oils (Adhi Santika, 1996). One type of fertilizer that is known to increase soil nutrients is organic fertilizer. Organic fertilizer in liquid form is one type of fertilizer that can be an option, in addition to facilitating the absorption of nutrients. Based on the results of laboratory analysis, it is known that the nutrient content contained in liquid organic fertilizer of rice washing water with onion skin does not meet the minimum technical standards under the Regulation of the Minister of Agriculture No. 70 of 2011 concerning organic fertilizers, biological fertilizers, and soil enhancers. Along with the results of the laboratory analysis, the POC of rice washing water with onion skin did not have a significant effect on the vegetative growth of cayenne pepper with concentrations of 50 and 75%.